First-Year Undergraduate Student Academic Profile: 2009 Enrollment - Krivickas, R.; Valinevičius, A.; Eidukas, D.; Andriukaitis, D.; Dekeris, B. (Elektronika ir Elektrotechnika, 2010)
Academic profile and performance, opinions about learning environment of the first year students’ is assessed and analyzed in order to increase effectiveness of education at the TEF. Results and discussion are based on survey data, collected aTEFr the first semester of study.